Bundles reduce anastomosis leak in patients undergoing elective colorectal surgery. A propensity score-matched study - Baeza-Murcia, M; Valero-Navarro, G; Pellicer-Franco, E; Soria-Aledo, V; Mengual-Ballester, M; Garcia-Marin, J. A; Betoret-Benavente, L; Aguayo-Albasini, J. L (Frontiers in Surgery, 2023)
Background: anastomosis leak still being a handicap in colorectal surgery. Bowel mechanical preparation and oral antibiotics are not a practice recommended in many clinical practice guides. The aim is to analyze the decrease in frequency and severity of postoperative complications, mainly related to anastomotic leak, after the establishment of a bundle. Methods: Single-center, before-after study. A bundle was implemented to reduce anastomotic leaks and their consequences. The Bundle group were matched to Pre-bundle group by propensity score matching. Mechanical bowel preparation, oral and intravenous antibiotics, inflammatory markers measure and early diagnosis algorithm were included at the bubdle. Results: The bundle group shown fewer complications, especially in Clavien Dindo´s Grade IV complications (2.3% vs 6.2% p<0.01), as well as a lower rate of anastomotic leakage (15.5% vs 2.2% p<0.01). A significant decrease in reinterventions, less intensive unit care admissions, a shorter hospital stay and fewer readmissions were also observed. In multivariate analysis, the application of a bundle was an anastomotic leakage protective factor (OR 0.121, p>0.05) Conclusions: The implementation of our bundle in colorectal surgery which include oral antibiotics, mechanical bowel preparation and inflammatory markers, significantly reduces morbidity adjusted to severity of complications, the anastomotic leakage rate, hospital stay and readmissions.